If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1b + -3b + -9 + -1(-4) = -17 Multiply -1 * -4 -1b + -3b + -9 + 4 = -17 Reorder the terms: -9 + 4 + -1b + -3b = -17 Combine like terms: -9 + 4 = -5 -5 + -1b + -3b = -17 Combine like terms: -1b + -3b = -4b -5 + -4b = -17 Solving -5 + -4b = -17 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -4b = -17 + 5 Combine like terms: -5 + 5 = 0 0 + -4b = -17 + 5 -4b = -17 + 5 Combine like terms: -17 + 5 = -12 -4b = -12 Divide each side by '-4'. b = 3 Simplifying b = 3
| -6x+2=-41 | | -2y+7=-9 | | 9(f+-6)=-15 | | 2+4v=8 | | f(x)=(3x^2+2x+1)6 | | 12x+-2y=-12x+755 | | 9.2t=6.3t-7.25 | | 60(17.5)+150y=1200 | | 12x+-2y=-12x+9 | | (x-32)/1.8=-35 | | (-16x^4)-(32x^3)-(80x^2)=0 | | 10+3k=22 | | 44=-5s+84 | | 60(7.5)+150y=1200 | | 2/3a-3/4=3/4 | | 33/4x5-4 | | 2+4v=18 | | -8y+23=3(y-7) | | 14-w/8=4x-9 | | 5n-7(n+3)=-25-2n | | -27a^4b^3/3ab | | 12+-2y=-12+-13 | | 1+s=3 | | -d/-12-6=1 | | 25=12a+61 | | 2(a+12)=50 | | 12+-2y=12+-13 | | 9[((9x9-10)/2)-5] | | 18X+18=16X+48 | | x-3.5=-2.5 | | 12+-2y=12+7y | | n=5m |